Strategi Peningkatan Kinerja Karyawan melalui Disiplin Kerja, Pelatihan, dan Pengembangan Karir: Studi Kasus di BCA KCU Palembang - Tampubolon, Miranda Roulina; Alie, Juhaini (Lembaga Penelitian, dan Pengabdian Kepada Masyarakat (LPPM) STIE GENTIARAS Bandar Lampung dan berkolaborasi dengan Ikatan Akuntan Indonesia Kompartemen Akuntan Pendidik (IAI KAPd), 2025)
In an era of competitive banking industry, improving employee performance is essential for company to achieve their strategic objectives. This study aims to analyze the effect of work discipline, training, and career development towards employee performance, both partially and simultaneously, among internship employees at PT Bank Central Asia, Tbk KCU Palembang. This study used a quantitative method by distributing questionnaires and conducting interviews. The sample consisted of 100 employees. Data were analyzed using SPSS version 20 through t-test and F-test. The t-test result shows that work discipline, training, and career development did not have a significant partial effect towards employee performance. However, the F-test result at a 5% significance level indicates that these three variables have a significant effect towards employee performance simultaneously. This study provides valuable insights for developing human resource strategies, particularly in strengthening training and career development based on discipline to improve employee performance. The findings may serve as a useful reference for future research and practical decision-making in managing internship employees in the banking sector.